Hip and Groin Injury Prevention in Elite Athletes and Team Sport – Current Challenges and Opportunities - Steven M. Short; Cameron W. MacDonald; Donald Strack (International Journal of Sports Physical Therapy)
Hip and groin injury (HAGI) has been reported as a source of significant time loss in elite sport. Field and court-based sports such as basketball, football, hockey, soccer, among others, require explosive multiplanar movement in single stance and high-speed change of direction. Often situations arise where sub-optimal pre-season training has occurred or congested in-season competition minimizes physiologic recovery periods between bouts of physical activity, both of which could magnify concomitant existing risk factors and increase injury risk. Identification and management of HAGI can be challenging as numerous structures within the region can be drivers of pain and injury, especially when considering the likelihood of concurrent pathology and injury reoccurrence. Focused prevention strategies have been suggested, but their practical clinical implementation has not been heavily investigated across the sporting spectrum. The purpose of this commentary is to review the historical and current state of HAGI, while focusing on applying evidence and clinical experience towards the development of future risk reduction strategies.